Space weather warning system - Hobbs, Stephen (Cranfield University, 2012)
Students of the MSc course in Astronautics and Space Engineering 2011–12 at Cranfield University studied a space weather warning mission for their group project. The mission was inspired by the Space Weather Diamond mission proposed by St. Cyr et al. in 2001. This report summarises the students’ work and their findings. The report consists of an overview and discussion of the technical work of the project and a compilation of the executive summaries which describe the specific contributions of each student. Two mission concepts are developed to provide at least 2 hours’ warning of severe space weather events. These are an augmented Space Weather Diamond mission and a Circular Heliocentric Constellation: both missions have advantages which justify further work.